Analysist The Value Chain Of Raw Material Rubber (Rmr) From Plantation Farmers’ Auctions To Market Channels - Bursamin Bursamin; Lina Widawati; Evi Andriani; Hilda Meisya Arif (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Objective: This study purposed for analyze value chain of raw material rubber (rmr) from plantation farmers’ auctions to market channels measuring market prices through natural rubber auctions. Methodology: this researced method used DSRS (Disproportion Stratified Random Sampling) technique, namely random sampling from population by conducting direct observation of rubber processor industry and analyzing value chain of raw material rubber based on market prices or base prices through the auction system. Results: The results analyzed of Value Chain of Raw Material Rubber (RMR) from Plantation Farmers’ Auctions to Market Channels inconsitance of the market price in the company's base price because the price through the auction system (7,000-9,000 IDR/ kgs), while the group system (10,500-12,500 IDR/ kgs). So that’s average selled value of farmers' rubber prices through of auction system is not balanced compared to selling value of farmers' rubber prices through the group system, to the average selling value of rubber prices (1,500 IDR/ Kgs). Conclusion: There are differences in the purchased system in the procurement of Rubber Processed Raw Materials Rubber (RMR) in the rubber industry at PT. Bukit Angkasa Makmur, Bengkulu Tengah Regency. The amount the Value Chain of Raw Material Rubber (RMR) from Plantation Farmers’ Auctions to Market Channels obtained by rubber farmers is not comparable between the auction system with average market price (874,447.50 IDR/week) and average group system (15.000-16.500 IDR/kgs), to average difference in the selling value of rubber (1,125,179.41 IDR/kgs). To prevent differences in the selling value of rubber prices for farmers in the middle of market prices, it is necessary to form farmer group units in each region so that the selling value of rubber processed materials increases and plays a role in increasing family income even though it is traditional in its marketing or through collectors so that the price received by farmers is relatively high. Type of Paper: Empirical Research Article.